2018
DOI: 10.1159/000487167
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of LncRNA AC067945.2 Down-Regulates Collagen Expression in Skin Fibroblasts and Possibly Correlates with the VEGF and Wnt Signalling Pathways

Abstract: Background/Aims: Long non-coding RNAs (lncRNAs) are thought to play crucial roles in human diseases. However, the function of lncRNAs in hypertrophic scar formation remains poorly understood. Methods: Utilizing qRT-PCR, we explored the expression changes of AC067945.2. Overexpression of AC067945.2 in normal skin fibroblasts was performed by transient plasmid transfection. Western blot was used to check the proteins' expression changes. Cell Counting Kit-8 (CCK-8) assay and Annexin V/7-AAD staining were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…A study by Chen et al (2018) investigated the role of long non-coding RNAs (lncRNAs) in hypertrophic scars and found that one lncRNA had lower levels (Chen et al, 2018). In cultured skin fibroblasts overexpressing this same lncRNA reduced COL3A1 mRNA levels.…”
Section: Regulation Of Col3a1 Expressionmentioning
confidence: 99%
“…A study by Chen et al (2018) investigated the role of long non-coding RNAs (lncRNAs) in hypertrophic scars and found that one lncRNA had lower levels (Chen et al, 2018). In cultured skin fibroblasts overexpressing this same lncRNA reduced COL3A1 mRNA levels.…”
Section: Regulation Of Col3a1 Expressionmentioning
confidence: 99%
“…Mechanistically, AC067945.2 can significantly promote early apoptosis and reduce the expression of COL1A1, COL1A2, COL3A1 and α‐SMA in normal skin fibroblasts. Therefore, downregulated AC067945.2 in hypertrophic scar tissues contributed to the pathological hypertrophic scar formation via inhibiting fibroblast apoptosis and promoting extracellular matrix deposition …”
Section: The Critical Role Of Lncrnas In Cutaneous Proliferation‐relamentioning
confidence: 99%
“…52,53 In skin fibroblasts, lncRNA AC067945.2 overexpression inhibited the expression of COL1A1, COL1A2, COL3A1. 54 Cao et al demonstrated that lncRNA PVT1 promotes atrial fibrillation by increasing collagen expression via the miR-128-3p-SP1-TGF-β1-Smad axis in atrial fibroblasts. 55 In this study, we identified a complex regulatory network of extracellular matrix-related genes, lncRNAs and miRNAs in the process of LGG recurrence.…”
Section: Discussionmentioning
confidence: 99%